Hubungan Antara Body Image Dengan Frekuensi Makan, Jenis Makanan Dan Status Gizi Remaja Putri Di Sma Negeri 7 Surakarta - Anggraeni, Sebtina Desty; , Dr.Mutalazimah,SKM.,MKes; , Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
Introduction: Adolescence is closely related to self-actualization. One is the familiar images of body shape or commonly called body image. In adolescence, to grow up very quickly. Body image in adolescents will strongly influence the selection of diets including groceries and eating frequency. A good diet should be formed in order to meet nutritional needs. A diet that does not comply will cause excessive nutrient intake or vice versa. Increased activities, social life and bustle teenagers, will affect their eating habits. Food consumption patterns are often irregular, frequent snacks, often do not have breakfast and lunch not yet. A balanced diet, which is in accordance with the requirements with the selection of the right foods will give birth to good nutritional status Objectives: To analyzed the relationship between Body Image with Meals Frequency, Type of Food and Nutritional Status of The girls in SMA Negeri 7 Surakarta Research Method: This research was an observational with cross sectional research design.The data body image obtained by used questionnaires, the data frequency and type of meals is obtained by FFQ for a month and the data obtained by measured the nutritional status of BB and Tb used the BMI. Subjects numbered 40 people taken by systematic random sampling. Statistical tests were used to analyzed the relationship is person corelation dan rank spearman a correlation test . Results: The majority of subjects positive body image that is equal to 52.5%. Research subjects who have a good meal frequency of 67.5% of the subjects who have the kind of good food by 45%. Most of the good nutritional status of the subject that is equal to 72.5% Conclusion: There is no relationship between Body Image with Meal Frequency, Type of Food and Nutritional Status of The girls in SMA Negeri 7 Surakarta